2021
DOI: 10.3390/toxins13030206
|View full text |Cite
|
Sign up to set email alerts
|

Wasp Venom Biochemical Components and Their Potential in Biological Applications and Nanotechnological Interventions

Abstract: Wasps, members of the order Hymenoptera, are distributed in different parts of the world, including Brazil, Thailand, Japan, Korea, and Argentina. The lifestyles of the wasps are solitary and social. Social wasps use venom as a defensive measure to protect their colonies, whereas solitary wasps use their venom to capture prey. Chemically, wasp venom possesses a wide variety of enzymes, proteins, peptides, volatile compounds, and bioactive constituents, which include phospholipase A2, antigen 5, mastoparan, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 174 publications
0
31
0
Order By: Relevance
“…Integrating transcriptomic and proteomic analyses should provide a better understanding of: the (i) venom composition of venomous hymenoptera in particular; and (ii) mammalian immune system responses to those stinging insects. It is hoped that this will assist in any future applications of venoms into diverse biomedicine and the possible discovery and development of new pharmacological agents and other related research areas [ 31 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Integrating transcriptomic and proteomic analyses should provide a better understanding of: the (i) venom composition of venomous hymenoptera in particular; and (ii) mammalian immune system responses to those stinging insects. It is hoped that this will assist in any future applications of venoms into diverse biomedicine and the possible discovery and development of new pharmacological agents and other related research areas [ 31 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Integrating transcriptomic and proteomic analyses should provide a better understanding of: the (i) venom composition of venomous hymenoptera in particular; and (ii) mammalian immune system responses to those stinging insects. It is to be hoped that this will assist any future applications of venoms into diverse biomedicine, and the possible discovery and development of new pharmacological agents, and other related research areas [31,[41][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Mastoparans are a group of amphiphilic peptides that are 14 amino acids long, with amidated C-termini, found in the venoms of a variety of social wasps [21]. Though toxic, or perhaps because of their toxicity, studies have shown mastoparans with potential therapeutic applications [22,23]. Mastoparan-like peptides have now been discovered in the venoms of solitary wasps as well [24].…”
Section: Introductionmentioning
confidence: 99%